Consequences of rising atmospheric CO₂ on ocean acidification and dissolved carbon cycling: a systematic review (Nepal Journal of Environmental Science, 2025)
Increasing atmospheric CO2 and temperature diminish ocean pH and raise the amounts of dissolved inorganic and organic carbons, causing wide-ranging shifts in marine water carbon chemistry and predicting the impacts on long-term ecosystems. This review aimed to determine the ocean chemistry and spatial variation of CO2 at a global scale, as well as to predict the influences of anthropogenic and natural changes on marine ecosystems. The literature has demonstrated that the southern polar oceans, Antarctica, and any coastal zone are predominantly susceptible to marine acidification and the dissolved carbon cycle. Based on 355 studies conducted over the last 30 years, this investigation found that marine acidification and the dissolved cycle are complex and poorly understood phenomena. These two facts and climate change are very interrelated, and the potential of these threats is very spatial, seasonal, stratified, and complex also. It was found that the atmospheric CO2 has increased by about 50% since preindustrial times and excess CO2 raise the seawater acidity through some equilibrium reactions in aqueous medium. The study observed that over the past half-century, the marine surface water acidity has risen by 30%, and predicted that by 2100, it will increase to 150. Moreover, this study critically reviewed the actual rules of marine dissolved organic and inorganic carbon on the global carbon cycle and marine acidification and vice versa. Such a major change in ocean chemistry will already have wide consequences for marine life and ocean ecosystems.